2017
DOI: 10.1088/1748-9326/aa897a
|View full text |Cite
|
Sign up to set email alerts
|

National- to port-level inventories of shipping emissions in China

Abstract: Shipping in China plays a global role, and has led worldwide maritime transportation for the last decade. However, without taking national or local port boundaries into account, it is impossible to determine the responsibility that each local authority has on emission controls, nor compare them with land-based emissions to determine the priority for controlling these emissions. In this study, we provide national-to port-level inventories for China. The results show that in 2013, the total emissions of CO, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 20 publications
7
42
0
Order By: Relevance
“…The breakdown of emissions from ship-related sources in Shanghai are shown in Table 3. Emission estimates from this study fall within the range of estimates from other studies (e.g., Fu et al, 2012Fu et al, , 2017. On the basis of shipping visa data, Fu et al (2012) determined that the total amounts of SO 2 , NO x and PM 2.5 in the vicinity of Shanghai Port in 2010 were 3.5×10 4 , 4.7×10 4 and 3.7× 10 3 t yr −1 , respectively, which is much lower than estimates in this study.…”
Section: Emissions From Different Ship-related Sources In Shanghaisupporting
confidence: 77%
See 1 more Smart Citation
“…The breakdown of emissions from ship-related sources in Shanghai are shown in Table 3. Emission estimates from this study fall within the range of estimates from other studies (e.g., Fu et al, 2012Fu et al, , 2017. On the basis of shipping visa data, Fu et al (2012) determined that the total amounts of SO 2 , NO x and PM 2.5 in the vicinity of Shanghai Port in 2010 were 3.5×10 4 , 4.7×10 4 and 3.7× 10 3 t yr −1 , respectively, which is much lower than estimates in this study.…”
Section: Emissions From Different Ship-related Sources In Shanghaisupporting
confidence: 77%
“…Based on the 2015 AIS data (the whole year), the annual emissions of SO 2 , NO x , PM 2.5 and VOCs from shipping sectors in YRD region were estimated at 2.2 × 10 5 t, 4.7 × 10 5 t, 2.7 × 10 4 t and 1.2 × 10 4 t, respectively, which accounted for 7.4 %, 11.7 %, 1.3 % and 0.3 % of the total emissions from all sources in the YRD in 2015, respectively. The emission estimates of SO 2 and NO x were close to the estimates of Fu et al (2017) for 2013, but estimates of SO 2 , NO x and PM 2.5 were slightly lower than those of Chen et al (2019) for 2014 due to the different temporal or spatial statistical scope. However, the proportion of ship SO 2 emissions in the YRD region with respect to the total Chinese shipping emissions in this study is consistent with the 33 % to 37 % reported in the other studies (Chen et al, 2017a(Chen et al, , 2019Liu et al, 2018b;Lv et al, 2018).…”
Section: Shipping Emissions In the Yrd Regionmentioning
confidence: 56%
“…When the domain was further limited to a regional scale, e.g., East Asia, the contribution of SO 2 and NO x emissions at berth increased to 26 % (Liu et al, 2016). When focusing on the national costal area the proportion of emissions from ships at berth continued to increase, reaching over 28 % (Fu et al, 2017). An in-port shipping emission inventory of Yangshan Port in China (Song, 2014) revealed that auxiliary engine exhaust contributed 40.5 and 43.3 % to overall PM 2.5 and SO x emissions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It contains a UV spectrometer covering the wavelength range between 300 and 380 nm with a full width at half maximum (FWHM) of 1 nm. It has a high spatial resolution of 50 × 50 km 2 and high time resolution of daily global coverage (Dittman et al, 2002;Seftor et al, 2014;González Abad et al, 2016). Its Equator crossing time in the ascending node is 13:30 LT.…”
Section: Omi and Omps Satellite Datamentioning
confidence: 99%